Study on the antibacterial activity of dandelion leaf tea. Issue 1 (March 2021) - Li, Shuhuan; Chi, Xiaojun; Bo, Yongheng; Zheng, Mengyao
Abstract: In this paper, Shandong dandelion tea was selected as the research object. Its water-soluble and fat-soluble components were extracted by alcohol precipitation method and Soxhlet extraction method, respectively. Antibacterial effects were tested on four different types of strains including Staphylococcus aureus (S.A), Salmonella (SE), Escherichia coli ( E. coil ) and Candida albicans (CA) in vitro by coating and drilling method. Results showed that dandelion tea powder had certain bacteriostatic effect on Staphylococcus aureus, Escherichia coli, Salmonella and Candida albicans . Water-soluble components mainly had bacteriostatic effect on Staphylococcus aureus, Salmonella and Escherichia coli, and showed the strongest bacteriostatic effect on Staphylococcus aureus but nearly no bacteriostatic effect on Candida albicans . Fat-soluble components had obvious bacteriostatic effect on Candida albicans, but not on Staphylococcus aureus and Escherichia coli .